Animal models for studying the etiology and treatment of low back pain. Issue 5 (14th March 2018) - Shi, Changgui; Qiu, Sujun; Riester, Scott M.; Das, Vaskar; Zhu, Bingqian; Wallace, Atiyayein A.; van Wijnen, Andre J.; Mwale, Fackson; Iatridis, James C.; Sakai, Daisuke; Votta‐Velis, Gina; Yuan, Wen; et al.
ABSTRACT: Chronic low back pain is a major cause of disability and health care costs. Effective treatments are inadequate for many patients. Animal models are essential to further understanding of the pain mechanism and testing potential therapies. Currently, a number of preclinical models have been developed attempting to mimic aspects of clinical conditions that contribute to low back pain (LBP). This review focused on describing these animal models and the main behavioral tests for assessing pain in each model. Animal models of LBP can be divided into the following five categories: Discogenic LBP, radicular back pain, facet joint osteoarthritis back pain, muscle‐induced LBP, and spontaneous occurring LBP models. These models are important not only for enhancing our knowledge of how LBP is generated, but also for the development of novel therapeutic regimens to treat LBP in patients. © 2017 Orthopaedic Research Society. Published by Wiley Periodicals, Inc. J Orthop Res 36:1305–1312, 2018.